The Study of The Variations Effect of Tngiston Lamp Lightening on Standard Deviation for the Captured ImagesVia Web Camera (ENET) - Alassadi, Z. I. H.; Kathem, F. J.; Jawad, H. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The system of work has been built , which consists of dark box with dimensions      (61 cm ï‚´74 cm ï‚´120 cm) when the distance between the testing image and the light source is (120   cm) .                                                                                                             We studied the white testing image (A4 paper) put in the box which is possible to control on the light inside it by electric system respected to tenkisten lamp .   The homogenous of light has been studied on the x and y axis for different image and light intensities . Then standard deviation has been studied for color bands RGB and intensity L for a recorded images and study its change as a function of applied power on the light system .  Our conclusion is that the constant value for the extracted  lines on the x and y axis respectively equal to zero (when the tenkisten lamp did not give sensitive light) , so the web camera did not sense low intensity then the sensitive of the web camera start when the power is greater than (0.001492 watt) and the standard deviation value still without change in the low intensity which in the volts are less than (60 volt) and the powers less than (0.001492 watt) . Observe the oscillation in the standard deviation value in the high power this can be considered as sensing characteristics of the web camera sensors properties (ENET) . Also ; observed with increasing power the mean ï increase and in the high light intensities arrangement accord in the mean specially in the  power larger than (0.005803 watt) .